As eleições diretas para diretores de escolas públicas municipais em Uberlândia: 2000 - 2004 - Domingues, Elzimar Maria (2010)
The present study is inserted in the research line - Public Politics and Management in Education of the Mastering Program in Education of the Federal University of Uberlandia. Its goal is to comprehend the historical construction of the process of Direct Election of Principals for Public Municipal Schools in Uberlandia, between the years 2000-2004. It also analyzes critically the political-pedagogical and ideological impacts of this process in the school routine. Since its creation, in the late 80 s, the Public Municipal Group of Education from Uberlandia-MG RPME/UDI (Rede Pública Municipal de Ensino de Uberlândia-MG) was a target of political-party management related organically to the executive power, which oriented, ideologically, the indication of jobs of school management to attend, authoritative and physiologically, interests of the class hegemonically dominant in the city. Given the relevance of this historical construction, the present qualitative research was based methodologically on the principals of Dialectical and Historical Materialism. The research promoted the documental analysis (of the Organical Municipal Law of Uberlandia LOM 1992, of the Commitment Letter to the Development of Public Municipal Education of Uberlândia 2000, of the Government Program of the Connection Now it is Zaire 2001-2004, of the Program Citizen School of the government Zaire Rezende 2001- 2004, of the Law of Elections for Principals in the city of Uberlandia Law 216/2001, and later regulamentation Law 7.832/01 and also of the letter of political pedagogical principles 2003-2004). It also examined a set of semi-structured interviews, organized in focal groups constituted of educators directly and indirectly involved in the process of construction and fulfillment of school elections in RPME/UDI. The discourse formations of the interviewee pointed to the initial acknowledgement that this process happened in a complex and contradictory juncture, permeated by fragmented actions of the municipal power, which reflected critically, in the process of the law elaboration that institutionalized the school elections (Law 216/2001), as well as in its implementation. The law mentioned counted, actively, with the participation of SINTRASP, rightful representative union of the category, in that time, the managers of SME, direct representatives of school units and the popular elected mandates in the city council and segments related to the educational sphere of UFU. Two elections for the job of management occurred between 2001 and 2004, and from this experience the interviewees confirmed, among other aspects, the fact that the construction of the democratic school management doesn t depend exclusively on the election of principals. That it must be consubstantiated in the adoption of public politics of education professional value, financial and administrative decentralization, as well as the effective political will of the established powers to give the school units the real autonomy of management. In 2007, the Public Ministry pointed out the unconstitutionality of the law 216/2001, fact that was used by the new municipal management elected for the period of 2005-2008, to justify and transform the election process in a consultation to the education professionals , which was interpreted by the interviewees as a profound throwback in the walk towards democratization in the schools of RPME/UDI.